2017
DOI: 10.3389/fnins.2017.00181
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MicroRNA in the Modulation of the Melanocortinergic System

Abstract: The central control of energy balance involves a highly regulated neuronal network within the hypothalamus and the dorsal vagal complex. In these structures, pro-opiomelanocortin (POMC) neurons are known to reduce meal size and to increase energy expenditure. In addition, leptin, a peripheral signal that relays information regarding body fat content, modulates the activity of melanocortin pathway neurons including POMC-, Agouti-related peptide (AgRP)/Neuropeptide Y (NPY)-, melanocortin receptors (MC3R and MC4R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 70 publications
(98 reference statements)
0
29
0
Order By: Relevance
“…More precisely, POMC-induced stimulation of BAT thermogenesis occurs following downstream melanocortin activation of sympathetic projections via MC4-R-expressing neurons located in the paraventricular nucleus of the hypothalamus and hindbrain [47][48][49]. In addtion, it has been clearly established that leptin increase thermogenesis and body temperature through activation of the POMC neurons and then the sympathetic nerves that control BAT activity [1,47,49]. In PDKO mice, we observed the induction of the expression of genes controlling fatty acid oxidation (Pparα, Pgc1α and Mcad) as well as thermogenesis (Dio2 and Ucp1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More precisely, POMC-induced stimulation of BAT thermogenesis occurs following downstream melanocortin activation of sympathetic projections via MC4-R-expressing neurons located in the paraventricular nucleus of the hypothalamus and hindbrain [47][48][49]. In addtion, it has been clearly established that leptin increase thermogenesis and body temperature through activation of the POMC neurons and then the sympathetic nerves that control BAT activity [1,47,49]. In PDKO mice, we observed the induction of the expression of genes controlling fatty acid oxidation (Pparα, Pgc1α and Mcad) as well as thermogenesis (Dio2 and Ucp1).…”
Section: Discussionmentioning
confidence: 99%
“…The hypothalamus is involved in the monitoring of the modifications in metabolic parameters (blood glucose and lipids) and/or hormones (insulin or leptin) and elicits adaptive responses like food intake regulation or autonomic nervous system modulation [1]. Within the arcuate nucleus (ARC) of the hypothalamus, pro-opiomelanocortin (POMC) neurons are the first to respond to the circulating signals of hunger and satiety such as leptin, insulin, ghrelin or glucose [1][2][3][4][5][6][7][8]. In accordance with the pivotal role of the melanocortin system in the control of food intake, it has been shown that the disruption of the POMC and melanocortin receptor 4 (MC4R) genes in mice models causes obesity [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the developing hypothalamus, important changes in the expression pattern of miRNAs have been described, suggesting the involvement of miRNAs in the functional organisation of the melanocortin system . Also, there is evidence showing that leptin, a hormone whose signal transduction pathway is downregulated in DIHI, modulates the hypothalamic expression of miRNAs and, conversely, miRNAs could modulate leptin signalling . The importance of miRNA‐mediated control of gene expression is demonstrated by the conditional deletion of Dicer, a key enzyme in miRNA processing.…”
Section: New Cellular Mechanisms Involved In the Development Of Hypotmentioning
confidence: 99%
“…The regulation of energy expenditure involved hormonal (leptin and insulin), metabolic (nutrients), and nervous signals [1,2]. The various signals mentioned before are integrated by the hypothalamus and the brainstem [1,2].…”
Section: Introductionmentioning
confidence: 99%